Ethnomathematics: Playful hydraulics from the geometric figures of awajún ceramics - Estela Urbina, Ronald Omar (2022)
The objective of this research is to reassess the mathematical knowledge that is evidenced in Awajún ceramics and link them as a playful strategy for teaching canal hydraulics to civil engineering students of the "Fabiola Salazar Leguía" National Intercultural University of Bagua. The methodology used consisted of conducting observational and descriptive studies. The relevance of the approach lies in describing the ancestral practices and customs of a given community in relation to its cultural context. The research was developed in three stages: i) Documentary review, as well as graphic and virtual sources of information on Awajún ceramics. ii) Samples of Awajún ceramics were collected and interviews were conducted with Awajún women. iii) Profiles of hydraulic channels were elaborated whose reference are the geometric figures that appear in the Awajún ceramics molded in pieces of the tangram. Likewise, some ceramic designs were digitized. The results obtained were the systematization of the information regarding the inputs used for the elaboration of the Awajún ceramics, as well as the identification of the geometric figures that appear recurrently in this ceramic, mainly in the piníg and amamuk. It is concluded that, in the Awajún ceramics, it is evident that its inhabitants have an elementary knowledge of geometry, mainly of the circle, triangle and lines. and that, using the pieces of the tangram, based on the triangle of the geometric figures of Awajún pottery, it is shown that the hydraulic radius is the best in trapezoidal channel conditions.